NUTRIENT DIGESTIBILITY AND GROWTH PERFORMANCE OF BROILER CHICKENS FED PROCESSED TROPICAL SICKLE POD (SENNA OBTUSIFOLIA (L) SEED MEAL - Clement, Augustine; Dankasa, Kwari Ibrahim; Uchei, Igwebuike Joseph; Bala, Adamu Shuaib; Siaka, Diarra Seriba (Journal of Agricultural Sciences (Belgrade), 2017)
Eight weeks feeding trial was conducted to evaluate the nutrient digestibility and growth performance of broiler chickens fed raw or processed Senna obtusifolia seed meal (SOSM). Six experimental diets were compounded to contain 0% SOSM and 20% each of the raw, boiled, soaked, sprouted and fermented SOSM respectively. Two hundred and sixteen (216) broiler chicks were randomly allotted to six (6) dietary treatments in a randomized complete block design with three (3) replicates containing 15 chicks each. Data were collected on nutrient digestibility, feed intake, weight gain, feed conversion ratio and mortality. The result of productive performance indicated that feed intake, weight gain and feed conversion ratio were significantly (P<0.05) depressed in broiler chickens fed raw, soaked and sprouted Senna obtusifolia seed meal. However, broiler chickens fed fermented SOSM showed superior (P<0.05) productive performance that is close to those fed the positive control diet (0% SOSM). The mortality rate did not reveal any particular trend. However, the low mortality rate recorded in the different treatments indicated broiler chicken can tolerate up to 20% of either raw or processed SOSM. Broiler chickens fed raw SOSM recorded lower values for dry matter (63.06%), crude protein (52.46%), ether extract (53.88%), crude fibre (30.72%) and nitrogen-free extract (46.11%) digestibility than those fed the other processed SOSM. The nutrient digestibility of broiler chickens fed fermented SOSM were significantly (P<0.05) better followed by those fed boiled Senna obtusifolia seed meal. For instance, broiler chickens fed FSOSM recorded the highest crude protein and ether extract of 69.91 and 70.03% compared to the other processing methods. It can be concluded that 20% fermented SOSM can be incorporated in the diets of broiler chickens without depreciation in biological performance. Slightly lower levels of boiled SOSM can be included in the diet of broiler chickens but the levels can be ascertained in further studies.